2023
DOI: 10.1037/emo0001161
|View full text |Cite
|
Sign up to set email alerts
|

Pleasant emotional feelings follow one of the most basic psychophysical laws (weber’s law) as most sensations do.

Abstract: Emotion episodes may include a conscious aspect of the emotion, namely being aware of our own emotional experience. Despite explosion in research over previous years, it remains unclear how emotions reach awareness and become feelings. Already in 1884, William James argued that emotional feelings resemble ordinary sensations in this respect. Here, using a novel model-based ratio scale of emotion intensity, we provide one of the strongest pieces of evidence supporting James' perceptual theory by showing that em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 41 publications
5
17
4
Order By: Relevance
“…Adapted from "Pleasant Emotional Feelings Follow One of the Most Basic Psychophysical Laws (Weber's Law) as Most Sensations Do," by R. Berkovich and N. Meiran, 2023, Emotion, 23(5) we were able to draw from the model both the intensity and the uncertainty measure of the emotional experience. Berkovich and Meiran (2023) predicted that both pleasant and unpleasant emotions would obey Weber's Law, but contrary to our predictions, Weber's Law was found only for pleasantness. Specifically, it was found that the uncertainty about pleasant emotional feeling increased with pleasant intensity, while uncertainty of unpleasant emotional feeling increased with pleasantness instead of increasing with unpleasantness.…”
Section: Berkovich and Meiran's (2023) Analysis And Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…Adapted from "Pleasant Emotional Feelings Follow One of the Most Basic Psychophysical Laws (Weber's Law) as Most Sensations Do," by R. Berkovich and N. Meiran, 2023, Emotion, 23(5) we were able to draw from the model both the intensity and the uncertainty measure of the emotional experience. Berkovich and Meiran (2023) predicted that both pleasant and unpleasant emotions would obey Weber's Law, but contrary to our predictions, Weber's Law was found only for pleasantness. Specifically, it was found that the uncertainty about pleasant emotional feeling increased with pleasant intensity, while uncertainty of unpleasant emotional feeling increased with pleasantness instead of increasing with unpleasantness.…”
Section: Berkovich and Meiran's (2023) Analysis And Resultscontrasting
confidence: 99%
“…The results in the "negative" group were in opposite direction to our prediction and to Berkovich and Meiran's (2023) results. These results seem to suggest that which, pleasant or unpleasant obeys Weber's Law depends on how we instruct participants to report.…”
Section: Increasing Sample Sizecontrasting
confidence: 99%
See 3 more Smart Citations